Promoting Early Childhood Development through Combining Cash Transfers and Parenting Programs - Arriagada, Ana-Maria (World Bank, Washington, DC, 2018)
This paper examines the potential for bringing together cash transfer and parenting programs focused on child stimulation to boost child development, particularly for children ages 0-3 years. The paper reviews the rationale for linking both types of programs and the evidence to date on the impact of cash transfer programs, parenting programs, and their combination. The paper reviews the main operational features of 10 examples of combining cash transfer and parenting interventions and identifies four models for structuring the combination: integrated, convergence, alignment, and piggy-backing. The paper finds promising evidence for combining the interventions, where adding the parenting program to the cash transfer program has improved some parental practices and child development outcomes, with results in cognition and language. However, the evidence is still scarce, and more research is needed to understand the key elements of the optimal combinations, fidelity of implementation, cost-effectiveness of different design features, replicability, and sustainability of results.